A New Complementary Touch for the Temporal Inverted Internal Limiting Membrane Flap Technique - Levent Karabas; Ecem Önder Tokuç; Sevim Ayça Seyyar; Özlem Şahin (Journal of Ophthalmic & Vision Research)
The temporal inverted internal limiting membrane (ILM) flap technique was developed to improve vitreoretinal surgery for large macular holes (MH). However, in addition to the difficulty of the surgical procedure, the main concern is the displacement of the ILM flap due to small fluid leakage into the posterior pole, even in the short time required to close the sclerotomies after fluid–air exchange. A new approach to the temporal inverted ILM flap technique is described here. In this approach, when the ILM flap is inverted over the MH, ILM forceps, while it is closed, are gently pressed over the folded edge and passed over ( just like folding a paper in half), creating an ILM fold mark like the ones used in origami. Thus, it can be seen that the minimal fluid leaking into the posterior pole ventilates the free edge of the flap, but the force formed along the folded edge prevents the flap turnover.